Neuroendocrine hyperplasia of infancy; a rare form of childhood interstitial lung disease: a case report - Saman, Uroosa; Haque, Anwarul; Mansoor, Mohammad; Arshad, Mohammad (Journal of the Pakistan Medical Association, 2022)
Interstitial lung disease in infancy is rare. In this case report, we discuss the case of a six-week-old male infant presented with persistent tachypnoea, retraction and mild hypoxaemia corrected by low-dose supplemental oxygen since the age of 2 weeks old. Birth history was unremarkable. Routine workup was done which turned out to be non-contributory. The child received multiple rounds of antibiotics along with bronchodilators and corticosteroids. There was no evidence of severe gastroesophageal reflux. Computed tomography of chest showed ground glass appearance, which was especially prominent in the right middle lobe and lingula ,and accompanied with air trapping. He was managed with mild respiratory supportive care, without positive pressure ventilation and nutritional management. He was discharged home, with instructions for in clinic follow up. A distinctive topographical picture and typical clinical symptoms were consistent with neuroendocrine hyperplasia of infancy (NEHI), which has a favorable prognosis. —Continue